碳纳米管海绵捕获循环肿瘤细胞 (2023)
本发明提供了在不使用癌症生物标志物的情况下，捕获来自对象的循环肿瘤细胞(CTC)的方法。所述方法包括使测试样品与碳纳米管(CNT)海绵接触。所述测试样品包含来自对象的去除血浆并裂解红细胞之后的少量外周血的细胞。所述测试样品中的细胞包含来自所述对象的CTC。所述CNT海绵不含特异性针对癌症生物标记物的试剂。 The present invention provides a method of capturing circulating tumor cells (CTCs) from a subject without using a cancer biomarker. The method comprises contacting a test sample with a carbon nanotube (CNT) sponge. The test sample comprises cells from a small amount of peripheral blood from a subject after removal of plasma and lysis of erythrocytes. The cells in the test sample comprise CTCs from the subject. The CNT sponge is free of an agent specific for a cancer biomarker.